Role of Tet2 in Regulating Adaptive and Innate Immunity - Li, Jiaqi; Li, Lifang; Sun, Xiaoxiao; Deng, Tuo; Huang, Gan; Li, Xia; Xie, Zhiguo; Zhou, Zhiguang (Frontiers in Cell and Developmental Biology, 2021)
Accumulated evidence indicates that epigenetic modifications play central roles in gene expression regulation and participate in developing many autoimmune and autoinflammatory diseases. Mechanistically, epigenetic modifications act as a bridge between environmental and cellular factors and susceptibility genes. DNA methylation is a critical epigenetic modification that is regulated by ten-eleven translocation (TET) enzymes. Accumulating evidence has revealed that TET family proteins function as gene regulators and antitumor drug targets mainly because of their ability to oxidize 5-methylcytosine (5mC) to 5-hydroxymethylcytosine (5hmC). Recently, the effect of Tet2, an essential TET protein, on the development of autoimmune diseases has been explored. In this review, we summarize the current understanding of Tet2 in immune response regulation, clarify the mechanisms of Tet2 in B and T cell differentiation and function, and discuss the opposing effects of Tet2 on inflammatory gene expression in the immune system to provide new potential therapeutic targets for related diseases.